Upaya Meningkatkan Hasil Belajar Muatan Bahasa Indonesia pada Tema Benda di Sekitarku Melalui Model Pembelajaran Course Review Horay di Kelas III SD Negeri 94/X Lagan Ulu Tahun Pelajaran 2022/2023 - Suwatni Suwatni (Journal on Education, 2022)
The main problem in this study is the low learning outcomes of students which is indicated by the average daily test scores below the KKM that has been set. The purpose of this study was to obtain information and discuss efforts to improve learning outcomes in Indonesian content on the theme of things around me through the course review horay learning model in Class III SD Negeri 94/X Lagan Ulu in the 2022/2023 academic year. This type of research is Classroom Action Research. This research was conducted at SD Negeri 94/X Lagan Ulu. The subjects referred to in this study were students in Class III of SD Negeri 94/X Lagan Ulu, a total of 10 students in semester I (odd) in the 2022/2023 school year. The data collection techniques used in this study were field note techniques, student worksheets, observations, and documentary evidence. The technique used in analyzing the collected data is descriptive quantitative with percentage calculations and data is reduced through data reduction and inference from the results of the analysis. The conclusion from this study is that learning by applying the course review horay cooperative learning model has a positive impact on improving the learning outcomes of students in Class III SD Negeri 94/X Lagan Ulu for the 2022/2023 academic year in Indonesian content through the act of giving rewards